1995
DOI: 10.1099/0022-1317-76-3-529
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human papillomavirus seroconversions

Abstract: The temporal relationship between primary genital human papiUomavirus (HPV) infections and the induction of antibodies against viral antigens has not been established. In order to address this question we studied a cohort of 110 women and 48 men with multiple heterosexual partners, who were followed for 220 person-years during which they made 583 visits to the sexually transmitted diseases clinic of the Amsterdam Public Health Service. At each visit spatula or brush samples from multiple anogenital and oral si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 21 publications
(18 reference statements)
2
27
0
Order By: Relevance
“…For HPV-16, this is in good agreement with previous studies that have mostly reported sensitivities of 50 % or greater (Kirnbauer et al, 1994 ;Chua et al, 1996 ;de Gruijl et al, 1997 ;Dillner et al, 1996 ;Wideroff et al, 1995 ;Wikstro$ m et al, 1995). For HPV-18 and -33 seropositivity, the present study provides the first large-scale evaluation of sensitivity and type-specificity, which were found to be similar to HPV-16.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For HPV-16, this is in good agreement with previous studies that have mostly reported sensitivities of 50 % or greater (Kirnbauer et al, 1994 ;Chua et al, 1996 ;de Gruijl et al, 1997 ;Dillner et al, 1996 ;Wideroff et al, 1995 ;Wikstro$ m et al, 1995). For HPV-18 and -33 seropositivity, the present study provides the first large-scale evaluation of sensitivity and type-specificity, which were found to be similar to HPV-16.…”
Section: Discussionsupporting
confidence: 92%
“…Presence of cervical HPV DNA is usually transient Evander et al, 1995 ;Hildesheim et al, 1994), is correlated with recent partner change (Hildesheim et al, 1993) and shows declining prevalence with age (Melkert et al, 1993). In contrast, presence of HPV antibodies in serum is also found after clearance of viral DNA (Wikstro$ m et al, 1995 ;Carter et al, 1996), the antibody levels persist on prolonged follow-up (af Geijersstam et al, 1998) and there is no consistent association of HPV seropositivity with age (Chua et al, 1996 ;Dillner et al, 1996 ;Wikstro$ m et al, 1995 ;. Also, HPV seropositivity is not related to recent partner change, but strongly dependent on lifetime number of sexual partners (linear increase of seroprevalences with about 4 % per partner) (Dillner et al, 1996 ;Wideroff et al, 1996), arguing that seroprevalences are preferable as markers of lifetime cumulative HPV exposure (Olsen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although IgG seroconversion against HPV-16 has been reported within 6 -12 months of infection (Wikstrom et al, 1995;Carter et al, 2000), the duration of serologic detection (e.g. being seropositive) remains unclear (Stone et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…So-called ' falsepositives ' may have occurred because the PCR technique has failed to detect HPV DNA in an infected individual due to sampling error or because the individual was infected at a site other than that which was biopsied. The absence of a detectable ELISA response may be explained by the possibility that the serological response may not peak until days or weeks after infection has been established and there is some evidence that the latter is true (Wikstrom et al, 1995). Alternatively, the B cell response may be sustained after the virus infection has been cleared because antigen is retained in the regional lymph nodes, for example.…”
Section: Discussionmentioning
confidence: 99%